Solution of the Magnetohydrodynamics Jeffery-Hamel Flow Equations by the Modified Adomian Decomposition Method (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, the nonlinear boundary value problem (BVP) for the Jeffery-Hamelflow equations taking into consideration the magnetohydrodynamics (MHD)effects is solved by using the modified Adomian decomposition method. We firsttransform the original two-dimensional MHD Jeffery-Hamel problem into an equivalentthird-order BVP, then solve by the modified Adomian decomposition method foranalytical approximations. Ultimately, the effects of Reynolds number and Hartmannnumber are discussed.